Atypical Anti-GBM with ANCA Vasculitis- A Rarest of the Rare Entity: Index Case from Eastern India - Rathod, Gopambuj Singh; Pal, Atanu; Mahato, Pallavi; Roy, Aakash; Sengupta, Debroop; Ahmad, Muzzamil (Journal of Clinical Nephrology, 2024)
Anti-glomerular basement membrane (GBM) antibody glomerulonephritis is an extremely rare glomerular disease. Around 90% of the patients are positive for serum anti-GBM antibodies while up to 10% can be negative. In such patients, only a kidney biopsy can reveal the anti-GBM disease it is then labeled as an atypical anti-GBM disease. Though anti-GBM disease can be associated with Anti Neutrophil Cytoplasmic Antibodies (ANCA) positivity, it is extremely rare to find atypical anti-GBM with ANCA positivity so much so that till now there are very few such cases reported from across the world. The case presented here is one such case where the patient presented with adult-onset nephrotic syndrome features with active urinary sediments and mildly deranged renal function. Myeloperoxidase (MPO) ANCA was positive and it was considered ANCA-associated crescentic glomerulonephritis (GN) but after the renal biopsy the picture was of anti-GBM disease. She was treated with pulse methylprednisolone but her creatinine increased in the meantime and considering anti-GBM she was put on Plasma Exchange (PLEX). She received 5 sessions of PLEX after which her renal function improved. She was also planned for Rituximab which could not be given due to local infection. As there are no protocols for treating such cases because of the extremely rare nature of the presentation, this case will increase the understanding of such presentations for the clinicians. This will help to plan for building the approach for such cases.